2003
DOI: 10.1083/jcb.200209057
|View full text |Cite
|
Sign up to set email alerts
|

Pointed-end capping by tropomodulin3 negatively regulates endothelial cell motility

Abstract: Actin filament pointed-end dynamics are thought to play a critical role in cell motility, yet regulation of this process remains poorly understood. We describe here a previously uncharacterized tropomodulin (Tmod) isoform, Tmod3, which is widely expressed in human tissues and is present in human microvascular endothelial cells (HMEC-1). Tmod3 is present in sufficient quantity to cap pointed ends of actin filaments, localizes to actin filament structures in HMEC-1 cells, and appears enriched in leading edge ruf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
110
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 46 publications
4
110
1
Order By: Relevance
“…Experimental observations further increase the relevance of such questions: Fashena et al (2002) showed that keratocyte-like movements occur in MCF7 breast adenocarcinoma cells overexpressing HEF1 (a cas-family protein), with the formation of a large leading lamellipod, enhanced ruffling and pronounced trailing edge. Similar observations were made in human microvascular endothelial cell line, HMEC-1 (Kiosses et al, 1999;Fischer et al, 2003). More surprisingly, Asano et al (2004) reported that the deletion of a single gene, amiB, from Dictyostelium cells, transforms this typically amoeboid cell to a crescent-shaped keratocyte-like cell with persistent movement and higher velocity.…”
Section: Robustnesssupporting
confidence: 68%
“…Experimental observations further increase the relevance of such questions: Fashena et al (2002) showed that keratocyte-like movements occur in MCF7 breast adenocarcinoma cells overexpressing HEF1 (a cas-family protein), with the formation of a large leading lamellipod, enhanced ruffling and pronounced trailing edge. Similar observations were made in human microvascular endothelial cell line, HMEC-1 (Kiosses et al, 1999;Fischer et al, 2003). More surprisingly, Asano et al (2004) reported that the deletion of a single gene, amiB, from Dictyostelium cells, transforms this typically amoeboid cell to a crescent-shaped keratocyte-like cell with persistent movement and higher velocity.…”
Section: Robustnesssupporting
confidence: 68%
“…more Tmod3 would lead to more F-actin and less Tmod3 to less F-actin. Moreover, despite the presence of a large soluble pool of Tmod3 at endogenous levels, these motile cells contained an abundance of free pointed ends (26). These observations suggested the existence of novel actin regulatory mechanisms for Tmod3, and/or other binding partners available to Tmod3 that prevented it from capping a subset of the actin pointed ends in cells.…”
mentioning
confidence: 82%
“…For example, in stable actin structures like the cardiac muscle sarcomere, Tmod1 regulation of actin exchange at pointed ends controls thin filament lengths and stability (23), such that the lack of Tmod1 in mice is lethal because of defective sarcomere assembly and aborted cardiac development (24,25). Conversely, in dynamic actin networks such as the lamellipodia of motile endothelial cells, Tmod3 is present in concentrations similar to other actin regulators, such as ADF/cofilin, and acts as a negative regulator of cell migration (26). As yet, Tmod3 is the only protein known to perform this negative regulatory function in dynamic actin networks like those found in lamellipodia (10).…”
mentioning
confidence: 99%
“…The blots were then incubated for 12-18 h at 4°C with 1-2 µg/ml of purified Tmods or TMs in OverWash supplemented with 2% BSA, and excess protein was rinsed with five 5-min washes with OverWash. Bound Tmods or TMs were detected by incubating blots for 12-18 h at 4°C with, as indicated, mouse monoclonal anti-Tmod1 (mAb95; 1 µg/ml; Almenar-Queralt et al, 1999a,b), affinity-purified rabbit anti-chicken Tmod4 (2 µg/ml; Almenar-Queralt et al, 1999b), rabbit antisera to human Tmod3 (R5168; 1:100; Fischer et al, 2003), or rabbit polyclonal antibodies to human erythrocyte TMs (R14; Ursitti and Fowler, 1994). Blots were then rinsed with two consecutive OverWash rinses followed by five 10-min shaking washes.…”
Section: Blot Overlaymentioning
confidence: 99%